1997
DOI: 10.1086/516163
|View full text |Cite
|
Sign up to set email alerts
|

Why Is Chronic Lyme Borreliosis Chronic?

Abstract: Chronic Lyme borreliosis (CLB) can present not only in different organs but also in different patterns. Although many theories exist about the mechanisms leading to CLB, it is known that viable Borrelia burgdorferi can persist for decades and cause late skin manifestations of acrodermatitis chronica atrophicans (ACA). Thus, the immunopathogenetic findings in ACA can serve as a model for studying the chronic course of Lyme borreliosis. Recent findings indicate that the most important cell for antigen presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
(15 reference statements)
0
15
0
Order By: Relevance
“…Cysts have been observed in vitro in human CSF (Brorson & Brorson, 1998a) and in vivo in the tissues of Lyme-disease-infected humans (Aberer et al, 1997 ;Hulinska et al, 1994). It is not known whether the cysts observed in those studies are the same as the cysts described in this report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cysts have been observed in vitro in human CSF (Brorson & Brorson, 1998a) and in vivo in the tissues of Lyme-disease-infected humans (Aberer et al, 1997 ;Hulinska et al, 1994). It is not known whether the cysts observed in those studies are the same as the cysts described in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Brorson & Brorson (1997) demonstrated that cells of B. burgdorferi undergo a morphological transformation from motile spirochaetes into non-motile, spherical cyst-forms when incubated for "4 weeks in BarbourStoenner-Kelly (BSKII) medium without the addition of rabbit serum, a routinely added media supplement thought to provide cells with a source of fatty acids (Barbour & Hayes, 1986). Cyst-forms have also been observed in Lyme disease patient tissues (Hulinska et al, 1994 ;Aberer et al, 1997). It has been reported that these forms of B. burgdorferi are viable and capable of transforming back into motile spirochaetes, although survival was not accurately quantified (Brorson & Brorson, 1997).…”
Section: B Burgdorferi Cells Alternate Between Tick Vectorsmentioning
confidence: 99%
“…Borrelia spirochetes can persist in the human body for prolonged periods, even for decades, as shown in patients with acrodermatitis chronica atrophicans (ACA) 3 lesions (6). In some patients with chronic disease, immune or other less wellcharacterized mechanisms are the cause of the symptoms.…”
Section: Lysine-dependent Multipoint Binding Of the Borrelia Burgdorfmentioning
confidence: 99%
“…Fact: B. burgdorferi assumes different forms in different hosts [41][42][43][44][45][46][47] . The most troublesome is the so-called cyst form that may lie dormant in the human host, thus evading antibiotic therapy that targets replicating bacteria [41][42][43][44][45] .…”
Section: Introductionmentioning
confidence: 99%
“…The most troublesome is the so-called cyst form that may lie dormant in the human host, thus evading antibiotic therapy that targets replicating bacteria [41][42][43][44][45] . The non-replicating cyst form is undoubtedly the key to persistence of infection with the Lyme disease spirochete, and any antibiotic approach to Lyme disease that fails to recognize this pathogenic entity may fail to eradicate the infection, leading to chronic disease [46,47] .…”
Section: Introductionmentioning
confidence: 99%